TESTING STUDY AND DYNAMIC ANALYSIS OF DRIVE TRAIN ON MW WIND TURBINE - YAN HongWen; TIAN HongQi; ZHAO Ping; YANG Liu; WANG YongSheng (Jixie qiangdu)
Drive Train is a key component. It is very important to analysis of dynamic for design and control on drive train vibration of wind turbine. So,from the multi body dynamics（ MBS） perspective,combined with the theory of rotor dynamics and modal,SIMPACK professional dynamics software as a simulation platform,a certain type of 2 MW wind turbine high precision drive chain model was established. Then,the characteristic frequency and the kinetic properties of the drive train were analyzed.Last,the analytical results were verified through site test unit.